2017
DOI: 10.3390/ijms18030541
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Exposure Gene Expression in Baboons with and without Pancytopenia after Radiation Exposure

Abstract: Radiosensitivity differs in humans and likely among primates. The reasons are not well known. We examined pre-exposure gene expression in baboons (n = 17) who developed haematologic acute radiation syndrome (HARS) without pancytopenia or a more aggravated HARS with pancytopenia after irradiation. We evaluated gene expression in a two stage study design where stage I comprised a whole genome screen for messenger RNAs (mRNA) (microarray) and detection of 667 microRNAs (miRNA) (real-time quantitative polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In addition to rhesus and cynomolgus macaques, several studies have been conducted using baboons (Papio sp) to investigate radiation injuries resulting from exposure to X-rays [9], 60 Co γ-radiation [10,11], and mixed field (neutron and γ-photon) irradiation [12]. In recent years, various studies have reported significant biomarkers for radiation injuries using the baboon model [1317]. Furthermore, a number of promising radiation countermeasures under development for H-ARS are being tested in NHPs for efficacy and pharmacokinetics/pharmacodynamics (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rhesus and cynomolgus macaques, several studies have been conducted using baboons (Papio sp) to investigate radiation injuries resulting from exposure to X-rays [9], 60 Co γ-radiation [10,11], and mixed field (neutron and γ-photon) irradiation [12]. In recent years, various studies have reported significant biomarkers for radiation injuries using the baboon model [1317]. Furthermore, a number of promising radiation countermeasures under development for H-ARS are being tested in NHPs for efficacy and pharmacokinetics/pharmacodynamics (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the baboons were placed in restraint chairs, sitting orthogonally, front to a horizontal and homogeneous field of gamma rays delivered by a 60 Co source (IRDI 4000; Alsthom, Levallois, France) to perform either total body irradiation (TBI) or partial body irradiation (PBI). In order to attain different patterns of PBI, a 20 cm thick lead screen was used to shield different parts of the body (for details see 20 , 21 . Two baboons were exposed to 5 Gy TBI and two others to 2.5 Gy TBI.…”
Section: Methodsmentioning
confidence: 99%
“…Two baboons were exposed to 5 Gy TBI and two others to 2.5 Gy TBI. Eight different exposure patterns were simulated and two baboons were exposed per pattern which summed up to 14 baboons receiving PBI (for details see 20 , 21 ) corresponding to an equivalent TBI dose of 2.5 or 5 Gy. Two dose rates were used (8 cGy/min for 5 Gy TBI and 5 Gy 50% PBI, and 32 cGy/min for all other situations) because the Cobalt 60 source was changed during this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has extensive experience in the isolation of RNA from whole blood, its cellular subgroups and biopsies of different tissue sources [20][21][22][23][24] . We recently became interested in isolating RNA from saliva.…”
mentioning
confidence: 99%